Web GIS-Based Forecasting of Earthquakes Using Fuzzy Time Series Method - Abdullah, Dahlan; Fajriana; Erliana, Cut Ita; Chaizir, Muhammad; Putra, Arwin (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Earthquake Forecasting is the process of predicting the possibility of an earthquake in a particular area using earthquake data from the previous year (this study uses earthquake data for 2017-2021). Aceh is one of the areas in Indonesia that is prone to disasters in terms of the frequent occurrence of earthquakes in several areas whose impacts are pretty severe. With this research, it is hoped that it can contribute to BMKG in particular and the community, in general, to find out the possibility of earthquakes occurring at several points in Aceh to be more alert in the future. This WebGIS-based Earthquake Forecasting application in Aceh was built using DFD (Data Flow Diagram) modeling and the PHP programming language and MySQL database as well as the Google Maps API. This Earthquake Forecasting Application uses the Fuzzy Time Series method in carrying out the calculation process. Fuzzy Time Series is a method with the solution being carried out in stages, and from that stage, the forecasting results for several areas in Aceh are found based on previous data; in this method, the process of searching for possible error values ​​is also carried out using AFER (Average Forecasting Error Rate) if the value The smaller the error, the more accurate it is. So that the forecasting results are found with the data of strength (magnitude), latitude, and longitude.